The Development Potential of Regional Programs : An Evaluation of World Bank Support of Multicountry Operations - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This evaluation examines the track record of the regional development programs that the World Bank has supported over the past 10 years. While these are relatively few in number, together they offer valuable lessons for how such programs can be designed and implemented to deliver good outcomes. This evaluation, which assesses World Bank support for regional development programs over fiscal years 1995-2005, finds that a majority of the programs evaluated have been or appear likely to be effective in achieving most of their development objectives. Even stronger results could be achieved if support for regional programs were better developed as an international aid practice. These findings are based on evaluations of 19 regional programs and a review of the Bank's total portfolio of some 100 regional operations. The IEG report assessed the World Bank's support for regional development programs active between fiscal years 1995 and 2005. These accounted for less than 1 percent of total Bank financing during this period. Three key findings are: (i) regional programs can deliver strong results; (ii) success and sustainability depend on strong ownership of all participating countries; and (iii) the Bank has been particularly effective in fostering country interest in regional programs through analytical work and resource mobilization, and less effective in helping countries deal with their conflicting interests and plan for sustainable activities. The evaluation identified five design features that have proven critical to the success of regional programs: strong country commitment, scope of objectives matched to national and regional capacities, clear delineation and coordination of the roles of national and regional institutions, accountable governance arrangements, and planning for sustainability. The evaluation concluded that the Bank has an opportunity to adopt a potentially bigger role, building on examples of successful experience. To do so, the evaluation recommended that the Bank: (i) establish regional program strategies and integrate them into Country Assistance Strategies (CASs); (ii) work with partners to put together grant and loan financing packages for individual regional programs; (iii) give more attention to improving the impact of Bank support for regional partnerships; and (iv) strengthen corporate incentives and capacities to provide effective regional program support.